A case study of Digi telecommunications Sdn Bhd strategic marketing analysis / Rohanizan Md Lazan ... [et al.] - Md Lazan, Rohanizan; Ali, Roslina; Abd Malik, Shaherah; Zainal Abidin, Rabiatul Alawiyah (2012)
This study will evaluate the strengths of Digi Telecommunication Sdn Bhd marketing strategy in order to establish competitive edge between its competitors. The finding of this study will in some way enable Digi Telecommunication Sdn Bhd to retain its position in the telecommunication industry.